Rostrupomyces, a new genus to accommodate Xerocomus sisongkhramensis, and a new Hemileccinum species (Xerocomoideae, Boletaceae) from Thailand - Santhiti Vadthanarat; Bhavesh Raghoonundon; Saisamorn Lumyong; Olivier Raspé (MycoKeys, 2024)
A new genus, Rostrupomyces is established to accommodate Xerocomus sisongkhramensis based on multiple protein-coding genes (atp6, cox3, tef1, and rpb2) analyses of a wide taxon sampling of Boletaceae. In our phylogeny, the new genus was sister to Rubinosporus in subfamily Xerocomoideae, phylogenetically distant from Xerocomus, which was highly supported as sister to Phylloporus in the same subfamily Xerocomoideae. Rostrupomyces is different from other genera in Boletaceae by the following combination of characters: rugulose to subrugulose pileus surface, white pores when young becoming pale yellow in age, subscabrous stipe surface scattered with granulose squamules, white basal mycelium, unchanging color in any parts, yellowish brown spore print, and broadly ellipsoid to ellipsoid, smooth basidiospores. In addition, Hemileccinum inferius, also from subfamily Xerocomoideae, is newly described. Detailed descriptions and illustrations of the new genus and new species are presented.